HUMAN RESOURCE MANAGEMENT IN SPORT AND RECREATION - Chelladurai, P.; Kim, Amy (Human Kinetics, 2023)
This textbook provides readers a foundation in research and application of human resource management in the sport and recreation industries. It explains essential concepts in human resources specific to the sport and recreation industries. It focuses on the three groups of people who constitute human resources in sport and recreation organizations: paid professional workers, volunteers, and clients.